Academic Libraries Promotion Through Social Media: A Systematic Literature Review - Nur Sanny Rahmawati; Rahmi Rahmi (Program Studi Ilmu Perpustakaan UIN Alauddin, 2021)
Library promotion through social media is an integral part of library services, especially for academic libraries. Social media can inform the end-users of what library’s resources and services and give librarians an impression of users’ views and needs. This study aimed to determine the use of social media to promote academic libraries in Indonesia. This research used a qualitative approach, specifically a systematic literature review, and includes details about identifying the research questions, the literature search process, data synthesis and search results. Based on the scientific papers identified and reviewed, the majority of research was published in 2019. The most frequent social media platforms for library promotions were Facebook and Instagram. Academic libraries located in Yogyakarta carried out the most social media promotions. Obstacles to promoting libraries through social media in Indonesia were primarily due to internal factors of libraries.